Identifikasi Industri Kreatif Pada Subsektor Kerajinan Blangkon Guna Menghadapi Asean Economic Community (AEC) - Widiasari, Niken; , Muclison Anis, S.T., M.T; , Ida Nursanti, ST., M.Eng.Sc (2015)
Blangkon handicraft industry is one of the cultural heritage that must continue to be preserved. End of 2015 the entrepreneurs will be faced with a free market economy Masyarakakat ASEAN or ASEAN (MEA). Blangkon craft is one of the creative industries which have great potential to compete with the MEA. Blangkon craft industry center in the city of Solo is located in District Serengan, Surakarta or often called Kampung Blangkon. The purpose of this study was to determine the readiness of the craft industry Blangkon to face MEA. The method used in this research is descriptive method, which is done by identifying the profile by conducting a survey of spaciousness. To determine the readiness of MEA used four indicators are: a skilled workforce, the sustainability of the industry, the free flow of goods and government support. Measurement of skilled labor using Westinghouse adjustment approach by adopting the skill factor, whereas to determine the sustainability of the industry, the free flow of goods as well as government support using the results of interviews conducted with the head of department of industry and trade city of Surakarta. then after the analysis of the four indicators of achievement MEA, SWOT analysis to identify opportunities, the threat, strengths, and weaknesses faced by the artisans craft industry Blangkon. From the analysis we concluded that the craft Blangkon not ready to face the MEA, because only two indicators are already qualified to face the MEA, namely: skilled labor (SDM) and the free flow of goods. As for the sustainability of the industry and government support is not ready. In fact, government support is crucial for the sustainability of the industry.